(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
A person is said to be stigmatized when they are subjected to discredit, devaluation, and shame as a result of the characteristics or attributes that they exhibit. In most cases, the effects of stigma on a person’s social life are unpleasant and include feelings of alienation, rejection, marginalization, and discrimination. Stigma can affect a person’s illness and treatment, including their ability to get professional and suitable medical care for their condition, if it is connected to a health condition like mental illness. It has been pointed out that mental health professionals are not the only ones impacted by stigma; patients’ loved ones feel it, too. The cultural and contextual value systems of a society, which can shift over time and between different settings, have a significant impact on stigma. On the other hand, there is a paucity of data regarding the nature of the stigma that patients suffering from mental illness and nurses working in mental health care face in Iraq. These days, stigma’s aftereffects are so pervasive that they pose a threat to public health in nearly every Western nation. The fallout might range from social isolation to prejudice towards those with mental illness in the job or classroom. This leads to poor self-esteem and confidence, which in turn hinders social and occupational functioning and therapy for people with mental illness.